2004
DOI: 10.1177/014572170403000515
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse-Coaching Intervention for Women With Type 2 Diabetes

Abstract: This nurse-coaching intervention demonstrates promise as a means of improving self-management and psychosocial outcomes in women with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
192
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 106 publications
(199 citation statements)
references
References 48 publications
5
192
0
2
Order By: Relevance
“…13,17 Three of the five ineffective studies focused on a variety of diabetes-related topics. 11,14,20 Furthermore, the sample sizes of effective studies were usually higher compared with the sample sizes of the ineffective studies, except for the study by Sacco et al 18 As in the studies with dietary outcomes, four of the five studies measuring the frequency of selfmonitoring of blood glucose (SMBG) found positive effects with large ES, regardless of intervention type and method.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13,17 Three of the five ineffective studies focused on a variety of diabetes-related topics. 11,14,20 Furthermore, the sample sizes of effective studies were usually higher compared with the sample sizes of the ineffective studies, except for the study by Sacco et al 18 As in the studies with dietary outcomes, four of the five studies measuring the frequency of selfmonitoring of blood glucose (SMBG) found positive effects with large ES, regardless of intervention type and method.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the American studies had specific target populations: AfricanAmerican adults 11,12 and Latino/ Hispanic adults, who also had to meet additional criteria; 13 three studies only included women. 11,14,15 Sample sizes ranged from 36 to 279 (mean 127).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations